MENELUSURI MAKNA PENGGUNAAN PAKAIAN PUTIH KETIKA SHOLAT: Analisis Living Hadis Studi Kasus Jama’ah Syahadatain Cirebon - Anisatun Muthi'ah; Wasman Wasman; Amir Amir (UIN Siber Syekh Nurjati Cirebon, 2020)
This paper discuss about the research meaning a wear of white dress in religious practices such as shalat, dzikir and other carried out by Asy-Syahadatain congregation in Panguragan, Cirebon. Result of the study using phenomenological qualitative methods, it was found the answer that the wear of white dress when worship is a symbol of cleanliness and purity of self. Because white dress are more important and better when compared with other colors. Actually, this practice is not something new, or nor just ordinary tradition, but the sunnah of the Prophet. That is the habits of the Asy-Syahadatain congregation have legal legitimacy derived from the Prophet’s.